Donaciones y créditos concesionales: impacto en el desarrollo - Domínguez Martín , Rafael; Tezanos Vázquez, Sergio (Revista Española de Desarrollo y Cooperación, 2023)
This paper aims to enlighten the debate on the differential impact of grants and loans in development aid. To this proposal it is done a review of debate on economic rationality of loans (commercial and concessional) in opposition to donations, and outlines other factors that explain the rapid evolution of ODA towards donation. It also presents a new case study on the differential impact of grants and ODA loans in Latin America and the Caribbean (LAC) in the period 1992-2007.